Sharia Adherence Mosque Survey: Correlations between Sharia Adherence and Violent Dogma in U.S. Mosques - Mordechai Kedar; David Yerushalmi (Perspectives on Terrorism, 2011)
A random survey of 100 representative mosques in the U.S. was conducted to measure the correlation between Sharia adherence and dogma calling for violence against non-believers.  Of the 100 mosques surveyed, 51% had texts on site rated as severely advocating violence; 30% had texts rated as moderately advocating violence; and 19% had no violent texts at all.  Mosques that presented as Sharia adherent were more likely to feature violence-positive texts on site than were their non-Sharia-adherent counterparts.  In 84.5% of the mosques, the imam recommended studying violence-positive texts.  The leadership at Sharia-adherent mosques was more likely to recommend that a worshipper study violence-positive texts than leadership at non-Sharia-adherent mosques.  Fifty-eight percent of the mosques invited guest imams known to promote violent jihad.  The leadership of mosques that featured violence-positive literature was more likely to invite guest imams who were known to promote violent jihad than was the leadership of mosques that did not feature violence-positive literature on mosque premises.